Modified Bloom's Taxonomy: Perspective of a Doctor of Philosophy Scholar - Wafa Omer (Journal of Rawalpindi Medical College)
The educational landscape is constantly evolving; with it, the frameworks we use to assess and foster learning must adapt. One such framework, Bloom's Taxonomy, has been a cornerstone in education since its inception in 1956.1 It first offered a hierarchical picture of cognitive abilities, from basic recollection to intricate assessment. But in a time of multidisciplinary integration and quick technical breakthroughs, reviewing and adapting this taxonomy to fit modern educational requirements is essential. As a doctor of philosophy, I suggest a revised Bloom's Taxonomy that leads to the highest learning objective: integration into practice-based systems. As a PhD and post-doc, I regularly develop original ideas, but I think the hardest part is integrating them into practice-based systems. The healthcare system does not gain from the innovations that are developed since they are not incorporated into the system and eventually go away.